The problems of Kazakh art on pages of “Ana tili” newspaper - Batkeeva Б.Т. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
Nowadays “Ana tili” is the progressive printed media outlet. It covers very important issues of national language, culture and literature, as well as it highlights the significant role of Kazakh language in upbringing of younger generation inspired by patriotism, respect to the culture, history and customs. In this article thorough analysis of “Ana tili” newspaper materials, related to the problem of national art is represented. The author gives detailed description of the content, style and language which is used in the article, as well as the relevance and urgency of the topic.